Business leadership in South Africas 1994 reforms - Shapiro, Ian; Luce, Henry R. (London : SAGE Publications Ltd, 2017)
The democratic, multi-racial election of 1994 ended the apartheid era in South Africa. Leading up to that historic change, a group of white business leaders saw that their country might follow one of two paths. It might experience an overthrow of minority rule, ending up something like Cuba, with a revolution and nationalization of major industries and isolation from much of the world. Alternatively, it could follow a path something more like Brazil, which ended military leadership and redemocratized to tolerate social change and political crises while encouraging a dramatic business growth.
Originally published: Shapiro, I. (2013). Business leadership in South Africas 1994 reforms. 13-010. New Haven, CT: Yale School of Management, Yale University. Retrieved from: https://nexus.som.yale.edu/south-africa-transition/.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Apartheid -- South Africa; Blacks -- South Africa -- Economic conditions; Blacks -- South Africa -- Social conditions; South Africa -- Economic policy; South Africa -- Race relations